Optimalisasi Produksi Sari Kedelai Sehat dalam Upaya Pembinaan Ibu Rumah Tangga di Desa Kualu, Kecamatan Tambang, Kabupaten Kampar: Optimization of the Soybeans Milk Production in the Purpose of Housewives Empowerment in Kualu Village, Tambang District, Kampar Regency - Anisa Mutamima; Nurfatihayati Nurfatihayati; Panca Setia Utama; Edy Saputra; Rozanna Sri Irianty; Feblil Huda (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Mutiara Ayu is a Micro, Small, and Medium Enterprise (MSME) which was founded by a group of housewives in Mutiara Kualu 8 Housing, Kualu Village, Tambang District, Kampar Regency, which produces Healthy Soybean Extract. Since its establishment in November 2020, MSME Mutiara Ayu has been experiencing various problems in running its business. The University of Riau Abdimas team, in partnership with MSME Mutiara Ayu, provided assistance to solve the problems being faced in the form of increasing knowledge and skills to improve product quality and quantity. The community partnership scheme service program was carried out for two months, namely July – August 2022, involving Real Work Lecture (Kukerta) students. This program was carried out in several stages of implementation, namely: (1) The preparation stage includes coordination with partner MSMEs, analysis of business conditions, recruitment, briefing with the community service team and students, coordination with various related parties, identification of needs, and analysis of instruments, (2) The implementation phase includes the provision of instruments and training, technical guidance, and assistance. (3) The monitoring and evaluation phase includes coordination with partner MSMEs, village parties, and Kukerta students. The results achieved in the Kukerta-integrated Abdimas program are an increase in product quality and quantity as well as an increase in the knowledge and skills of MSME Partners related to production and business management, which is expected to increase Mutiara Ayu's MSME income in the future.